Identification of metabolites from Halamphora sp. and its correlation with quorum sensing inhibitory activity via UHPLC-ESI-MS/MS-based metabolomics and molecular networking - Abd Ghafar, Siti Zulaikha; Muthukrishnan, Sarmila; Zolkeflee, Nur Khaleeda Zulaikha; Natrah, Ikhsan (John Wiley and Sons Inc, 2025)
The UHPLC-MS/MS metabolomics approach was employed to profile and characterize multi-components in Halamphora sp. extracted with different solvents that contribute to quorum sensing inhibitory (QSI) activity. A total of 37 and 34 metabolites were tentatively identified from negative and positive ion modes, respectively. The metabolites have been assigned to various groups, including fatty acids, glycolipids, sterols, diazines, flavonoids, peptides, carotenoids, and pigments. Multivariate data analysis showed that the QSI activity in the acetone extract was due to tumonoic acid A, terpeptin derivatives, pheophorbide A, hydroxyhexadeca-1,5-dien-3-ynoxy]propane-1,2-diol, l-methionyl-l-tyrosine, stearidonic, hexadecadienoic, tricosenoic, palmitic, and linolenic acids. These metabolites were more concentrated and differed significantly in acetone extract compared to other extracts. Acetone extract displayed a cluster of nodulisporic acid and fucoxanthin through MS/MS-based molecular networking (MN) platform. The present study shows that the liquid chromatography mass spectrometry (LCMS)-based metabolomics and MN effectively identify QSI-active metabolites in Halamphora sp. extracts, which can be promoted as a natural antifoulant.